Оптимізація диспетчеризації генеруючих потужностей енергосистеми за умови обмеження генерації вітрових та сонячних електростанцій - Shulzhenko S.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2020)
To solve the actual task of finding optimal generation mix and dispatch of thermal and nuclear power units, and hydro units of hydro pumped storages of Ukraine to cover day load power profile according to one of possible wind and solar generation curtailment mode the modification of mathematical MIP model is proposed. There are three modes of wind and solar generation curtailment revised in the article: 1) absolute maximum generation curtailment, 2) single for whole day decreased load factor, and 3) one per one hour decreased load factor. The possibility to allocate an exogenously determined level of frequency containment reserves (secondary reserves) on thermal power units is realized in the MIP model.The calculation’s results analysis shows that among revised wind and solar generation curtailment methods the method 2) is most appropriate in the short term because only administrative measures implementation is required, which could be put into force with appropriate legislation and does not require essential investments or implementation of complicated technical measures. The additional possible positive effect caused by the implementation of method 2) is it makes background for participation wind and solar generation in the ancillary services market and intraday balancing. In the middle term, the gradual implementation of method 3) is the most appropriate decision because a more stable power system balancing mode (minimum import/export amounts) could be provided. Moreover, extra nuclear power units and fewer coal thermal power units could be dispatched that is decreases hazard pollutions and carbon emission.The MIP model is written using MathProg language, a freeware version of AMPL. As a solver, the GNU GLPK program is used. The overall time for one calculation with standard table PC is about 30 seconds. MIP model could be used both for short-term power system optimal dispatch and for long-term national generation mix development studies under the growth rates of renewable installed capacities.